Surface exfoliation analysis on single-crystal silicon under compressed plasma flow action. (12th March 2018) - Shen, J.; Shahid, I.; Yu, X.; Zhang, J.; Zhong, H.W.; Yu, X.; Huang, W.Y.; Liang, G.Y.; Cui, X.J.; Yan, S.; Zhang, X.F.; Le, X.Y.
Abstract: Surface exfoliation was observed on single-crystal silicon surface under the action of compressed plasma flow (CPF). This phenomenon is mainly attributed to the strong transient thermal stress impact induced by CPF. To gain a better understanding of the mechanism, a micro scale model combined with thermal conduction and linear elastic fracture mechanics was built to analyze the thermal stress distribution after energy deposition. After computation with finite element method, J integral parameter was applied as the criterion for fracture initiation evaluation. It was demonstrated that the formation of surface exfoliation calls for specific material, crack depth, and CPF parameter. The results are potentially valuable for plasma/matter interaction understanding and CPF parameter optimization.